2013
DOI: 10.1136/bmj.f7095
|View full text |Cite|
|
Sign up to set email alerts
|

Red flags to screen for malignancy and fracture in patients with low back pain: systematic review

Abstract: Objective To review the evidence on diagnostic accuracy of red flag signs and symptoms to screen for fracture or malignancy in patients presenting with low back pain to primary, secondary, or tertiary care. Design Systematic review.Data sources Medline, OldMedline, Embase, and CINAHL from earliest available up to 1 October 2013.Inclusion criteria Primary diagnostic studies comparing red flags for fracture or malignancy to an acceptable reference standard, published in any language.Review methods Assessment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
146
0
15

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 249 publications
(165 citation statements)
references
References 47 publications
4
146
0
15
Order By: Relevance
“…A recent paper summarizing two Cochrane diagnostic systematic reviews found nine studies evaluating the diagnostic accuracy of in total 29 red flags for fracture and 24 for malignancy [8]. There were differences in the red flags that demonstrated diagnostic utility and those endorsed by guidelines.…”
Section: Comparison With the Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…A recent paper summarizing two Cochrane diagnostic systematic reviews found nine studies evaluating the diagnostic accuracy of in total 29 red flags for fracture and 24 for malignancy [8]. There were differences in the red flags that demonstrated diagnostic utility and those endorsed by guidelines.…”
Section: Comparison With the Literaturementioning
confidence: 99%
“…For malignancy, the systematic review concluded that only 'history of cancer' is based on acceptable validity; it increases the probability of having cancer from 0.7 % (pretest) to 33 % (95 % CI 22-46 %) [8]. Nevertheless, this conclusion is based on one study set in primary care and another in an emergency department where 36 % of patients were referred to because of a significant trauma [40,41].…”
Section: Comparison With the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…The scoring for each item ranges from 0 (less than 1 day per week) to 3 (5 to 7 days per week). The scoring for items 2, 6,7,12, 14,16,18,20,21 and 23 is reversed.MZDI score = sum of all items.The range of the score is from 0 to 69 where higher score indicates more depressed. …”
mentioning
confidence: 99%